2021
DOI: 10.1155/2021/6739220
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Antimicrobial Susceptibility of Bacteria Isolated from Poultry Farms from 2014 to 2018

Abstract: The current situation of antibiotic resistance of most bacterial pathogens was a threat to the poultry and public health with increasing economic losses. Regarding this problem, monitoring of the circulating microorganisms occurred with the antibiotic resistance profile. A total of 657 different samples from internal organs (liver, heart, lung, and yolk) and paper-lining chick boxes were collected from native chicken farms which were submitted to the Reference Laboratory for Veterinary Quality Control on Poult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(18 reference statements)
2
5
0
Order By: Relevance
“…In the same study, resistance to tetracycline was detected in more than half of the isolates encoded by the tetK and tetM genes [47]. In our study, resistance to tetracycline was detected in 85.3% of the isolates, including all S. sciutri, S. urealyticus and S. haemolyticus, and in 25 out of 36 S. lentus, which was similar to the findings of other studies [28,31,48]. The high frequency of tetracycline resistance in poultry samples may be due to the fact that, according to the ECDC/EFSA/EMA report, tetracycline and penicillin were the most prescribed antibiotics for food-producing animals in 2017 [49].…”
Section: Discussionsupporting
confidence: 91%
“…In the same study, resistance to tetracycline was detected in more than half of the isolates encoded by the tetK and tetM genes [47]. In our study, resistance to tetracycline was detected in 85.3% of the isolates, including all S. sciutri, S. urealyticus and S. haemolyticus, and in 25 out of 36 S. lentus, which was similar to the findings of other studies [28,31,48]. The high frequency of tetracycline resistance in poultry samples may be due to the fact that, according to the ECDC/EFSA/EMA report, tetracycline and penicillin were the most prescribed antibiotics for food-producing animals in 2017 [49].…”
Section: Discussionsupporting
confidence: 91%
“…A lower MDR of 52.3% compared to our study was reported previously [67]. High-level resistance has also been documented [56,68,69]. This poses a severe public health threat due to the resistance to a broad range of antibiotics observed in this study and could be a consequence of continuous exposure and extensive usage of these antibiotics in these study areas [27].…”
Section: Plos Onesupporting
confidence: 42%
“…A further investigation was applied to detect the MDR pattern of the bacterial pathogen for a proper comprehension of the situation using Disc diffusion method by12 different antimicrobial discs of different antimicrobial groups, the results showed a complete resistance pattern of all the bacterial isolates to sulfamethazine, nalidixic acid and oxytetracycline. Harmonizing with Hamed et al (2021) who found that the greatest resistance from the salmonella and E. coli isolates collected from poultry farms in Egypt was to these antibiotics among others.…”
Section: Discussionmentioning
confidence: 99%